Neck pain and related factors in patients with rheumatoid arthritis. Issue 3 (19th May 2022) - Suzuki, Akinobu; Yamada, Kentaro; Yabu, Akito; Tamai, Koji; Takahashi, Shinji; Inui, Kentaro; Okano, Tadashi; Koike, Tatsuya; Nakamura, Hiroaki
ABSTRACT: Objectives: In rheumatoid arthritis, neck pain can be caused by inflammatory reactions or cervical lesions, but the prevalence and associated factors have not been well studied. This study aimed to investigate the prevalence of neck pain in patients with rheumatoid arthritis and elucidate the related factors. Methods: This study included 146 patients with rheumatoid arthritis. Neck pain, quality of life, and levels of anxiety and depression were evaluated using a questionnaire. Cervical lesions and spinal alignment were evaluated using plain radiograph and magnetic resonance imaging. Factors associated with neck pain were analysed using a logistic regression model. Results: Fifty-six per cent of the patients had neck pain, and the quality of life scores were significantly worse in these patients. Multivariate analysis revealed age, C7 sagittal vertical axis, upper cervical lesion, and endplate erosion as factors associated with neck pain in patients with rheumatoid arthritis. Conclusions: More than half the patients with rheumatoid arthritis suffer from neck pain, and neck pain affects the quality of life and activities of daily living. Neck pain was associated with upper cervical lesion and endplate erosion suggesting the importance of radiological examination in patients with rheumatoid arthritis and neck pain.